2011
DOI: 10.1007/s10856-011-4355-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface treatments on the adhesion of electrochemically deposited hydroxyapatite coating to titanium and on its interaction with cells and bacteria

Abstract: The effect of different mechanical and chemical pre-treatments on the adhesion strength of hydroxyapatite (HAp) coating on a commercially pure titanium (CP-Ti) substrate was studied by means of a standard tensile test followed by microscopic and chemical analysis to determine the locus of fracture. In addition, the effects of either these pre-treatments or post-treatment by low-energy electron irradiation, which allowed tuning the wettability of the surface, on both osteoblast progenitor attachment and S. aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…Furthermore, the nature, structure and chemical composition of the substrate surface also play an important role [36]. Besides, the adhesion strength of plasma-spayed deposits was found to decrease when either the plate power was reduced (from 28 to 22 kW) or the working distance was increased (from 90 to 130 mm) [186].…”
Section: Adhesion and Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the nature, structure and chemical composition of the substrate surface also play an important role [36]. Besides, the adhesion strength of plasma-spayed deposits was found to decrease when either the plate power was reduced (from 28 to 22 kW) or the working distance was increased (from 90 to 130 mm) [186].…”
Section: Adhesion and Cohesionmentioning
confidence: 99%
“…Positive effects were discovered for both the glow-discharge [69,70] and ultraviolet [47,70,71] pre-treatments of the same polymers. Other types of pre-treatments of various surfaces were found to influence as well [36].…”
Section: Adhesion and Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples labeled as B and M and were held by conductive carbon glue to a thin copper strip. The surface of the samples were cut before deposition of hydroxyapatite by sandpaper Hermes grit abrasives 1000 because it was shown at cpTi Gr.2 that the different surface treatment (grinding, etching, immersion, blasting or heat treatment) increases the adhesion of the electrochemically deposited coatings (44). Deposition of the coating parameters are listed in Table II.…”
Section: Preparation Of Hydroxyapatite Coatingmentioning
confidence: 99%
“…Various biocoatings have been proposed as effective methods for improving the bone-implant interface stability. In recent decades, hydroxyapatite ((Ca 10 (PO 4 ) 6 (OH) 2 ; HA) has been reported to have a high biocompatibility, a low degradation rate, and the ability to increase the efficiency of bone-implant integration in order to improve osteointegration of implants because of its similar composition to bone tissue and its ability tocreate chemical bonding withbones[9]. Xie and Luan[10] reported that the precoated HA could further improve the stability of the Ti6Al4V alloy with a composite layer of TiO 2 and HA.…”
Section: Introductionmentioning
confidence: 99%